The penetration and phenotype modulation of smooth muscle cells on surface heparin modified poly(ɛ‐caprolactone) vascular scaffold. Issue 10 (7th July 2017) - Cao, Jie; Geng, Xue; Wen, Juan; Li, Qingxuan; Ye, Lin; Zhang, Aiying; Feng, Zengguo; Guo, Lianrui; Gu, Yongquan
Abstract: The tubular porous poly(ɛ‐caprolactone) (PCL) scaffold was fabricated by electrospinning. After then, the scaffold's surface was firstly eroded by hexyldiamine to endow amine group, and heparin was covalently grafted to the surface to get surface heparin modified scaffold (ShPCL scaffold). It was found that ShPCL scaffold can induce smooth muscle cells (SMCs) to penetrate the scaffold surface, while the SMCs cannot penetrate the surface of PCL scaffold. Subsequently, the rabbit SMCs were seeded on the ShPCL scaffold and cultured for 14 days. It was found the expression of α‐smooth muscle actin in ShPCL scaffold maintained much higher level than that in culture plate, which implied the SMC differentiation in ShPCL scaffold. Furthermore, the immunefluorescence staining of the cross‐sections of ShPCL scaffold exhibited the expression of calponin in ShPCL scaffold can be detected after 7 and 14 days, whereas the expression of smooth muscle myosin heavy chain can also be detected at 14 days. These results proved that penetrated SMCs preferably differentiated in to contractile phenotype. The successful SMC penetration and the contractile phenotype expression implied ShPCL scaffold is a suitable candidate for regenerating smooth muscle layer in vascular tissue engineering. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2806–2815, 2017.